Penggunaan Aplikasi Zoom Meeting Dalam Pembelajaran Fiqih (Praktek Mengkafani Jenazah) Dimasa Pandemi - Niken Septantiningtyas; Ika Fitri Anwar (Edudeena : Journal of Islamic Religious Education, 2021)
Abstract: This study is intended to describe the effectiveness of the online learning process at MTs Nurul Iman during the pandemic in practical fiqh learning by using zoom application media. This research is a descriptive qualitative research type of field research conducted at the Madrasah Tsanawiyah Nurul Iman for one week with interview data collection techniques and observations of 9th-grade students of MTs Nurul Iman, school principals, and teachers of fiqh learning. In online learning of fiqh, the practice of using the zoom application can be said to be effective, Students feel more understanding and more confident, and independent. There are also obstacles such as network disturbances and the use of more quota packages than usual. The implications of the effectiveness of using Zoom Meetings in learning fiqh, the practice of shrouding corpses, can be said to be positive, where students become easy to understand in learning subjects, students also become more confident in their abilities, and students become more independent by learning using zoom meeting media. Abstrak: Penelitian ini ditujukan untuk menggambarkan efektifitas proses pembelajaran daring di MTs Nurul Iman selama masa pandemi dalam pembelajaran Fiqih praktek dengan menggunakan media aplikasi zoom meeting. Penelitian ini menggunakan pendekatan kualitatif deskriptif jenis penelitian lapangan yang dilakukan di lembaga Madrasah Tsanawiyah Nurul Iman selama satu pekan pengambilan datanya menggunakan teknik pengambilan data wawancara dan observasi terhadap siswa kelas 9 MTs Nurul Iman, kepala sekolah, serta guru pengajar pembelajaran Fiqih. dalam pembelajaran daring Fiqih praktek penggunaan aplikasi zoom meeting dapat dikatakan efektif, siswa merasa lebih faham dan lebih percaya diri serta mandiri. Terdapat juga hambatan-hambatan diantaranya gangguan jaringan dan penggunaan paket kuota yang lebih banyak dari pada biasanya. Implikasi efektifitas penggunaan Zoom Meeting pada pembelajaran Fiqih praktek mengkafani jenazah dapat dikatakan positif, dimana siswa menjadi mudah faham dalam mempelajari mata pelajaran, siswa juga menjadi lebih percaya diri dengan kemampuan mereka, serta siswa menjadi lebih mandiri dengan pembelajaran menggunakan media zoom meeting.